ANALISIS KONSEP DAN IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DALAM KURIKULUM MERDEKA - Muhajiroh, Ninik; Susanto, Susanto; Hanafi, Ilyas Rozak; Anwar, Khoirul; Kurniawan, Hariri (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2025)
ABSTRACT Islamic Religious Education is a learning process that aims to apply or realize Islamic teachings and values ??in everyday life. This is in line with research that shows that Islamic religious education is a conscious effort made by educators to foster and guide students in schools so that after completing their education they are able to understand, appreciate, and practice Islamic teachings. The research method used is a descriptive qualitative method through field research and data collection techniques consisting of observation, interviews and documentation as well as through triangulation analysis. The results of the study show that the Islamic Religious Education Curriculum at SMA Negeri 1 Kalirejo, Central Lampung has a significant impact on the development of character and understanding of Islamic values ??in students. With a more flexible approach, this curriculum allows students to be actively involved in the learning process that can strengthen students' faith and morals. Religious education plays an important role in the Indonesian educational landscape. This type of education emphasizes character development, especially the instillation of Akhlakul Karimah (noble morals) in students, which is an important foundation for the development of moral and personal integrity. However, religion-based education not only contributes to the formation of students' character, but also encourages the development of positive traits and performance in teachers, which ultimately contributes to increased satisfaction with the effectiveness of teacher teaching. ABSTRAK Pendidikan Agama Islam merupakan suatu proses pembelajaran yang bertujuan untuk menerapkan atau merealisasikan ajaran dan nilai-nilai Islam dalam kehidupan sehari-hari. Hal ini sejalan dengan penelitian yang menunjukkan bahwa pendidikan agama Islam merupakan suatu usaha sadar yang dilakukan oleh pendidik untuk membina dan membimbing peserta didik di sekolah agar setelah menyelesaikan pendidikannya mampu memahami, menghayati, dan mengamalkan ajaran-ajaran Islam. Metode penelitian yang digunakan dengan metode kualitatif deskriptif melalui penelitian lapangan dan teknik pengumpulan data terdiri dari obervasi, wawancara dan dekomentasi serta melalui analisis triangulasi. Adapun hasil penelitian menunjukkan bahwa Kurikulum Pendidikan Agama Islam di SMA Negeri 1 Kalirejo Lampung Tengah berdampak signifikan terhadap pengembangan karakter dan pemahaman nilai-nilai Islam siswa. Dengan pendekatan yang lebih fleksibel, kurikulum ini memungkinkan siswa terlibat aktif dalam proses pembelajaran yang dapat memperkuat keimanan dan akhlak siswa. Pendidikan agama memegang peranan penting dalam lanskap pendidikan Indonesia. Jenis pendidikan ini menitikberatkan pada pengembangan karakter, khususnya penanaman Akhlakul Karimah (akhlak mulia) pada peserta didik, yang menjadi landasan penting bagi pengembangan integritas moral dan pribadi. Namun demikian, pendidikan berbasis agama tidak hanya berkontribusi dalam pembentukan karakter siswa, tetapi juga mendorong pengembangan sifat-sifat dan kinerja positif pada diri guru, yang pada akhirnya berkontribusi pada peningkatan kepuasan terhadap efektivitas pengajaran guru.